Exploring Medicinal Plants for Antimicrobial Activity and Synergistic Effects With Doxycycline Against Bacterial Species - Joel Frank Kenmeni; Ibrahim Sifi; Borel Ndezo Bisso; Prudence Ngalula Kayoka-Kabongo; Ulrich Joël Tsopmene; Jean Paul Dzoyem (The Scientific World Journal)
Medicinal plants are rich sources of bioactive compounds with diverse pharmacological properties, including antimicrobial activities. This study aimed to assess the antibiofilm potential of methanol and ethanol extracts from nine selected medicinal plants, as well as their synergistic effects with doxycycline against Bacillus strains. Standard procedures were employed to determine the phytochemical composition, total phenolic, and flavonoid contents of the extracts. The antibacterial activity was evaluated using the broth microdilution method, while biofilm formation was assessed via the microtiter plate method. Antibiofilm activity was determined using the 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium-bromide (MTT) assay. Combination studies were conducted using the checkerboard microdilution method. All extracts contained phenols, flavonoids, steroids, triterpenes, and anthraquinones. The methanolic extract of Psidium guajava exhibited the highest total phenolic and flavonoid contents (90.48 ± 0.55 mg GAE/g), while the ethanolic extract of Olax subscorpioidea showed the highest flavonoid content (6.48 ± 0.33 mg QE/g). Ethanol extracts of Eucalyptus globulus and Psidium guajava and methanolic extract of Syzygium jambos demonstrated significant antibacterial activity against Bacillus anthracis 34F2 Sterne strains, with a MIC value of 64 μg/mL. Biofilm formation in Bacillus strains was notably enhanced in the presence of glucose. The methanolic extract of O. subscorpioides exhibited the highest biofilm imbibition (85%), while Picralima nitida methanolic extract showed the most effective biofilm eradication (79%). The combination of Solanum torvum ethanol extract with doxycycline displayed synergistic effects against biofilm formation inhibition and eradication in all tested Bacillus strains. Taken together, Solanum torvum ethanol extract shows promise for developing new combination antibacterial therapies.